(untitled) (SCIENCE TIME JOURNAL, 2026)
The growing internationalization of higher education has increased the importance of English communicative competence for students in non-philological disciplines, particularly in management education. Future managers are expected to communicate effectively in academic and professional contexts, including discussions, presentations, teamwork, and decision-making in English. However, existing General English courses often fail to address these discipline-specific communicative demands. This study aims to conduct a needs analysis of English communicative competence among undergraduate management students prior to any instructional intervention. Guided by the target needs framework, the research examines students’ necessities, lacks, and wants in relation to English communication. A quantitative descriptive design was employed, and data were collected through a structured questionnaire administered to management students at a higher education institution. The questionnaire focused on perceived communicative requirements, existing competence gaps, and preferred learning practices. The findings reveal that management students demonstrate high awareness of the importance of English communicative competence, particularly for oral communication in professional contexts. At the same time, they report significant communicative difficulties, especially in speaking fluently, expressing ideas confidently, and participating in discussions. Additionally, students express a strong preference for interactive, practice-oriented, and profession-specific learning activities, indicating dissatisfaction with traditional grammar-centered instruction. The study highlights a clear mismatch between communicative demands and students’ current abilities, underscoring the necessity of ESP-oriented instruction. The findings provide empirical support for incorporating needs analysis as a foundational step in designing English courses tailored to management students’ professional communication needs.